Hubungan Self Regulated Learning dengan Perilaku Menyontek Siswa pada Saat Ujian - Santika, Maria; Zikra, Zikra (MASALIQ, 2023)
Nowadays, cheating behavior occurs a lot among students, both from elementary to tertiary level. Cheating occurs because students tend to be lazy to think complexly and do not know how to use effective learning strategies including self regulated learning strategies. Self regulated learning is indicated by a person's ability to control and supervise himself, being able to make his own study schedule so that students have good learning management, where these things are expected to reduce students' desire to cheat. This study aims to describe the description of self-regulated learning and the description of students' cheating behavior during exams and to examine the relationship between students' self-regulated learning and students' cheating behavior during exams at SMP Negeri 36 Kerinci. This type of research is descriptive correlational. The population in this study were 106 students enrolled in the 2022/2023 academic year with a research sample of 84 students selected using the Stratified Random Sampling technique. Data collection uses a self-regulated learning questionnaire and a cheating behavior questionnaire with a Likert scale model. Data were processed using descriptive statistical analysis techniques and Pearson Product Moment correlational analysis techniques. The results of this study indicate that (1) the level of self-regulated learning of students at SMP Negeri 36 Kerinci is in the medium category, namely 72.6%, (2) the level of students' cheating behavior during exams at SMP Negeri 36 Kerinci is in the low category, namely 54.8% , (3) there is a negative and significant relationship between self-regulated learning and students' cheating behavior during exams at SMP Negeri 36 Kerinci with a correlation of -0.350 and a significance value of 0.001.